PENGARUH INOVASI PRODUK, CITRA MEREK, DAN WORD OF MOUTH (WOM) TERHADAP MINAT BELI KERUPUK KULIT BABI MENTAH TAKSU SNACK DI SURABAYA - Anak Agung Ngurah Tri Satyabimanyu; Auditia Setiobudi (Universitas Ciputra Surabaya, 2022)
The competition in food and beverage business keeps on increasing because being one of human basic needs. This increasing competition also transforms the consumers behavior in buying a product. Taksu snack is a business that runs in industry field of Balinese snack. The purpose of this is to find out the effect of product innovation, brand image and word of mouth on buying interest. The population uses potential consumers who know Taksu snack raw pork skin crackers and the sample of 96 respondents. The data analysis uses Validity test, Reliability test, Classical Assumption test, Multiple Linear Regression Analysis, Coefficient Technique Determination test, F test and T test that are processed by using the SPSS software. The questionnaire distribution through Google Form with 18 total question items, and the evaluation uses likert scale of 1-5. From the result of research it is obtained in which: (1) Product innovation affects significant positive on buying interest in which it is obtained of 0,000 value. (2) Brand image affects significant positive on buying interest in which it is obtained significant value of 0,000. (3) Word of mouth affects significant positive on buying interest in which it is obtained significant value of 0,000. The great effect of independent variables on buying interest is at 51,8%.